2011
DOI: 10.1007/s10474-011-0100-8
|View full text |Cite
|
Sign up to set email alerts
|

A note on weakly clean rings

Abstract: Let R be an associative ring with identity. An element x ∈ R is said to be weakly clean if x = u + e or x = u − e for some unit u and idempotent e in R. The ring R is said to be weakly clean if all of its elements are weakly clean. In this paper we obtain an element-wise characterization of abelian weakly clean rings. A relation between unit regular rings and weakly clean rings is also obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…We first begin with the promised above extension of Theorem 2.1 from [5], especially of the implication (⇒), in the sense of Definition 2.1 in [3]. Theorem 2.1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We first begin with the promised above extension of Theorem 2.1 from [5], especially of the implication (⇒), in the sense of Definition 2.1 in [3]. Theorem 2.1.…”
Section: Resultsmentioning
confidence: 99%
“…The sufficiency follows directly from [5], so that we will concentrate on the necessity. To that aim, given x ∈ R, then we may write x = u + f or x = u − f with u ∈ U (R) and f ∈ Id(R).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, by virtue of [20] or [24], a ring R is an exchange ring if, for every x ∈ R, there exists an idempotent e such that e ∈ xR and 1 − e ∈ (1 − x)R. It is well known that clean rings are exchange while the converse is untrue; for abelian rings these two sorts of rings, however, coincide. Generalizing this, in [29] (see [6] or [7] too) a ring R is said to be weakly exchange if, for each x ∈ R, there exists an idempotent e such that e ∈ xR and 1 − e ∈ (1 − x)R or 1 − e ∈ (1 + x)R. By the proof of the necessity of Theorem 2.1 from [6], it is well known that weakly clean rings are in general weakly exchange, but the converse manifestly fails. However, for abelian rings, in the cited theorem from [6] was shown that weakly exchange rings are precisely the weakly clean rings.…”
Section: Introductionmentioning
confidence: 81%